A decision support system for Ogoh-Ogoh assessment based on SMART and SAW methods in the context of Balinese cultural preservation - Adnyana, I Ketut Widhi; Fratiwi, Tria Hikmah (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2025)
Bali’s cultural richness includes the Ogoh-Ogoh tradition, which has recently evolved from a ritualistic practice into a competitive event evaluated through multidimensional criteria. However, the current manual evaluation process faces significant challenges, including subjective bias, inconsistent scoring standards, and inefficient data processing, which often reduce public trust in competition results. This study proposes a web-based Decision Support System (DSS) integrating the Simple Multi-Attribute Rating Technique (SMART) and Simple Additive Weighting (SAW) methods to enhance objectivity and transparency in Ogoh-Ogoh assessment. The system was implemented and tested using a dataset of 45 Ogoh-Ogoh alternatives. The comparative analysis demonstrates a strong consistency between the two methods, evidenced by a Spearman’s Rank Correlation coefficient of 0.81. Furthermore, performance testing revealed that the system achieved an 85% ranking accuracy compared to expert manual evaluations and significantly improved operational efficiency by reducing processing time by 40% (from 2.5 hours to 1.5 hours). These findings confirm that the proposed DSS not only minimizes subjectivity but also serves as a valid tool for the digitalization and preservation of cultural heritage assets.